“Tu con la testa, io con il cuore”: : the influence of Romanticism in the life and lyrics of Piero Ciampi - Giorgio, Alessandro (Scenari, 2021)
The paper offers an overview of the life and career of Italian singer-songwriter Piero Ciampi (1934-1980) through the main philosophical categories of Romanticism as it spread throughout Europe from the nineteenth century, in the belief that both the life of the artist and the lyrics of his songs are emblematic of that particular way of life promoted by Romanticism, based on the idea of artistic genius, the importance of subjective experience and the revaluation of faculties such as feeling, imagination and intuition. The work will also focus on the relationship between art and industry, discussing the idea that Piero Ciampi – in his difficult placement within the music industry – clearly embodies this relationship in its conflicting elements, previously highlighted from a theoretical point of view through reference to authors such as Theodor Adorno, Edgar Morin and Umberto Eco.